A novel carbonate as a diesel fuel additive. (3rd April 2017) - Guo, Hejun; Guo, Zhengxi; Liu, Shenghua
ABSTRACT: A new oxygenate 2, 2 / -diethoxyethyl carbonate was synthesized through transesterification using dimethyl carbonate and ethylene glycol monoethyl ether as raw materials and its chemical structure was identified through FT-IR, 1 H NMR, and GC-MS analyses. The oxygenate is miscible with individual hydrocarbons at normal temperature. When 2, 2 / -diethoxyethyl carbonate is added to diesel fuel, kinematic viscosity decreases slightly, smoke point increases linearly, flash point and solidifying point decline remarkably even at low content level of 5%(v), whereas they do not decrease further with the increase in its content level. When a diesel engine was fueled with a diesel fuel containing 25%(v) of the oxygenate, the smoke emissions were reduced up to 83.3%, the energy consumption was decreased by up to 15.5%, whereas the power output dropped noticeably at high speed.